2016
DOI: 10.1371/journal.pone.0165019
|View full text |Cite
|
Sign up to set email alerts
|

Step-Wise Increase in Tigecycline Resistance in Klebsiella pneumoniae Associated with Mutations in ramR, lon and rpsJ

Abstract: Klebsiella pneumoniae is a gram-negative bacterium that causes numerous diseases, including pneumonia and urinary tract infections. An increase in multidrug resistance has complicated the treatment of these bacterial infections, and although tigecycline shows activity against a broad spectrum of bacteria, resistant strains have emerged. In this study, the whole genomes of two clinical and six laboratory-evolved strains were sequenced to identify putative mutations related to tigecycline resistance. Of seven ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
3
36
3
Order By: Relevance
“…Deletion of the chromosomal β-lactamase of K. pneumoniae should allow clarification of whether piperacillin is expelled by pumps produced at normal levels. We found that AcrAB overproduction affects not only the activity of tigecycline, as previously described (Bialek-Davenet et al, 2015 ; Fang et al, 2016 ), but also that of ertapenem, piperacillin, ceftolozane, and temocillin. We also found that the MICs of ceftolozane+tazobactam were 4-fold lower than ceftolozane MICs in strains overproducing AcrAB.…”
Section: Discussionsupporting
confidence: 88%
“…Deletion of the chromosomal β-lactamase of K. pneumoniae should allow clarification of whether piperacillin is expelled by pumps produced at normal levels. We found that AcrAB overproduction affects not only the activity of tigecycline, as previously described (Bialek-Davenet et al, 2015 ; Fang et al, 2016 ), but also that of ertapenem, piperacillin, ceftolozane, and temocillin. We also found that the MICs of ceftolozane+tazobactam were 4-fold lower than ceftolozane MICs in strains overproducing AcrAB.…”
Section: Discussionsupporting
confidence: 88%
“…In order to investigate AcrAB-TolC efflux pump-dependent and pump-independent tigecycline resistance mechanisms, we analysed the sequences of the acrR , ramR , marR , soxR , lon , rpsJ and rpoC genes [ 25 , 26 ] by aligning our isolates with the reference genes of the tigecycline-susceptible isolate K. pneumoniae subsp. pneumoniae MGH78578 (GenBank Accession No.…”
Section: Resultsmentioning
confidence: 99%
“…The resistome of antimicrobial resistance genes was analysed using ResFinder-2.1 software (default identity thresholds [ID] 98%) provided by the Center for Genomic Epidemiology ( http://www.genomicepidemiology.org ) and the resources of the Pasteur MLST K. pneumoniae database, and by locally running the BLAST program. Previously described genes relating to AcrAB-TolC efflux pump-dependent and pump-independent tigecycline resistance mechanisms ( acrR , ramR , marR , soxR , lon , rpsJ and rpoC) [ 25 , 26 ], and chromosomal ( mgrB, pmrA/pmrB, phoP/phoQ ) and plasmidic ( mcr-1 and mcr-2 ) colistin resistance-related genes [ 27 , 28 ] were analysed in order to elucidate the possible determinants of tigecycline and colistin resistance. In the case of blaKPC -negative strains, the possible association between carbapenem resistance and the loss or alteration of outer membrane porins was investigated by studying the ompK35 and ompK36 genes.…”
Section: Methodsmentioning
confidence: 99%
“…The overexpression of AcrAB-TolC and OqxAB in clinical K . pneumoniae isolates without a history of tigecycline exposure may be due to exposure to other antimicrobials that are transported by the same efflux pumps 8 12 . The eravacycline-resistant and eravacycline-heteroresistant K .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, mutations in ramR , acrR , and rpsJ genes have also been reported to contribute to K . pneumoniae resistance to tigecycline 9 , 12 .…”
Section: Introductionmentioning
confidence: 99%